Studi Kelayakan Sebagai Langkah Awal Kesuksesan Bisnis (Studi Kasus Pada UMKM Rumah Organik) - Adinda Wulansari; Ayu Fitrianingtyas; Cindy Luthfiana Ganie; Dwi Intan Sari; Fina Widia Wulansari; Indah Aprilia Susanti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to determine and analyze the feasibility of an Organic Banana Chips House business using business feasibility measurement aspects, namely legal aspects, market aspects, finance, engineering/operations, management, economics and social. Apart from using these aspects, measuring business feasibility also uses the Net Benefit Cost Ratio (BCR). This research uses a qualitative method with a case study approach and the data source used is the primary data source in the form of interviews with the owner of the Rumah Organik Banana Chips business. Based on the business feasibility analysis using BCR at Rumah Organic Banana Chips, a measurement result of 0.95 was obtained, which means this business is categorized as a business worth maintaining in accordance with Faradiba & Musmulyadi (2020) which states that if BCR>0 then the business is worth maintaining